Pengembangan Kompetensi Dosen - Sowiyah Sowiyah (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2005)
The focus of this qualitative study is to describe the attempts made by Brawijaya University in developing its lecturers’ competence. Using snowball sampling, this study included data in the form of informa-tion from source people in the university and of relevant documents. The study revealed that the university encouraged its lecturers to further their study to both masters and doctoral degrees. In addition, the university offered certain rewards to the lecturers having their articles published in journals.